(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this study is to examine the nutritional knowledge, attitudes and practices of young athletes. 100 young athletes (male and female) from Mahatma Gandhi University in Kottayam, Kerala, India were selected for this study. The only age limit for participants is 18 to 23. Male athletes (n=50) and female athletes (n=50) were selected as two groups of 50 each. Standard questionnaire to evaluate participants’ knowledge, attitudes and practices on sports nutrition. The data obtained for the selected variables were subjected to the ’t’ test at a significance level of 0.05. The findings showed that there was a significant difference between boys and girls in choosing good nutritional knowledge, attitudes and practices. This finding suggests that boys outperformed girls in all aspects of the survey, including healthy eating habits, attitudes, and practices